Selection of a Core Collection for the Uruguayan maize germplasm collection of the blanco dentado race - Ozer-Ami, H.; Suárez, R.; Abadie, T. (Agrociencia Uruguay, 2004)
A Core Collection (CC) is a subset chosen to represent the genetic diversity of a germplasm collection with a minimun of redundancies. In this research, different sampling strategies were compared, and the best one was used to develop the Uruguayan Maize Core Collection of the Blanco Dentado race. The Uruguayan Maize Collection database came from the South American Maize Genetic Resources Catalog. A patter analysis was performed, which consists in a succession of cluster analysis and principal component analysis. The three groups identified in the patter analysis were used as sampling units. The number of accessions per group was defined based on the Relative Diversity method. Two kinds of CC were selected using different strategies: stratified sampling selection (pattern analysis) and random sampling selection as a control. The range retention of the stratified selection strategies was 10 % higher than random selection strategies. Range retention confirmed the results obtained concerning the superiority of the stratified selection strategies compared with the random selection.